Morocco : 2011 Article IV Consultation: Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Morocco. (IMF Staff Country Reports; Country Report, 2011)
This consultation paper explains that several years of sound macroeconomic policies and political reforms have left Morocco well equipped to address the 2008 international crisis and to respond to pressing social demands. In this challenging environment, Morocco has performed well economically and has seen its social indicators improve. It is stressed that containing and reorienting public expenditure, particularly by reforming the generalized subsidies system, will be the key to ensuring medium-term fiscal sustainability. A well-targeted subsidy system would be less costly and would better support the neediest segment of the population.